Correlation Between Characteristic Meteorological Drought and Climate Variability in Gunungkidul Regency Using SPI - Astrid Damayanti; Adyaksa Grahito Bagas Pamungkas; Riza Putera Syamsuddin (International Journal of Remote Sensing and Earth Sciences, 2025)
Meteorological droughts are the beginning of all kinds of droughts that can affect food security and human well-being, It can cause humans to move to other areas. Meteorological droughts are closely related to rainfall that can be affected by climate variabilities such as El Nino Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD), thus causing long drought conditions. Drought problems almost every year occur in Indonesia, including Gunungkidul Regency. Therefore, this research is expected to provide prevention of sustainable drought impacts and as a reference for further research. This study used data from a period of 30 years from 1991 to 2020 which included rainfall, sea level pressure (SLP), and sea surface temperature (SST) data. The Standardized Precipitation Index (SPI) was used in this study to characterize drought and classify drought levels with a time scale of 3 and 12 months. Climate variability was identified using the Southern Oscillation Index (SOI) for ENSO and the Dipole Mode Index (DMI) for IOD. Spatial descriptive analyses and statistical descriptive analyses are used to examine meteorological drought characteristics and patterns. In 30 years, Gunungkidul Regency faced drought events at least more than 70 times. Meteorological droughts tend to occur in areas that have elevation between 200 – 400 masl, 400 – 600 masl, 0 – 200 masl, and >600 masl. The meteorological drought in Gunungkidul Regency will get worse if there is an El Nino and Positive IOD phase simultaneously.